Impaired trophoblast invasion and increased numbers of immune cells at day 18 of pregnancy in the mesometrial triangle of type 1 diabetic rats. Issue 2 (February 2015) - Groen, B.; Uuldriks, G.A.; de Vos, P.; Visser, J.T.; Links, T.P.; Faas, M.M.
Abstract Introduction Type 1 diabetes (T1D) is associated with adverse pregnancy outcome, usually attributed to hyperglycemia. Recently, we showed that pregnancy outcome in normoglycemic T1D rats was characterized by decreased fetal and placental weight, suggesting impaired placental development. In the present study, we tested the hypothesis that trophoblast invasion and spiral artery (SA) remodeling is impaired in T1D rats ant that this is associated with aberrant local presence of NK cells and macrophages in the mesometrial triangle (MT). Methods Placentae with MT from pregnant biobreeding diabetes-prone (BBDP; T1D model) rats, control biobreeding diabetes-resistant (BBDR) and Wistar-rats were dissected at day 18 of gestation and stained for trophoblast invasion, SA remodeling, uNK cells and macrophages. Results Interstitial trophoblast invasion and SA remodeling was impaired in BBDP-rats vs. control rats, coinciding with increased presence of NK cells and an increased iNOS+/CD206+ ratio of macrophages. Discussion Decreased fetal and placental weight in BBDP-rats was associated with diminished interstitial trophoblast invasion and less optimal SA remodeling, increased numbers of NK cells and increased iNOS+/CD206+ macrophage ratio in the MT of BBDP-rats. Conclusions The impaired trophoblast invasion and SA remodeling may be due to an aberrant local immune-response and may result in damage to the fetal placenta and insufficient supply of nutrients towards the fetus with eventually decreased fetal weight as a consequence.